Modelling PFAS transport and mass discharge from the saturated zone: A case study of the fire drill site at Arlanda Airport - Hult,Emilia (2026)
Perfluoroalkyl substances (PFAS) are man-made, highly persistent and mobile compounds that have been extensively used in decades, for example as a fire repellent in aqueous film-forming foam (AFFF). They have been detected in soil, surface water and groundwater, where they pose risks to human health through contamination of drinking water supplies and to ecosystems. In this case study, PFAS spreading from a fire training site at Arlanda Airport was assessed by simulating perfluorobutanesulfonic acid (PFBS). This was done to estimate the contaminant mass in the saturated zone and predict the mass discharge to a nearby stream, while assessing the uncertainty of these predictions. Groundwater flow and PFBS transport were simulated using a numerical groundwater model in combination with a solute transport model (MODFLOW-2005 and MT3DMS) under a best estimate and a worst-case scenario, the latter based on high mass discharge to Kättstabäcken. The numerical groundwater model was calibrated against observed hydraulic heads, and sensitivity and uncertainty analysis were conducted using a limited set of Null Space Monte Carlo realisations. Results indicate that the median mass PFBS in the saturated zone is 39.1 g in the best estimate scenario and 5.50 g in the predicted worst-case scenario. The corresponding median mass discharge per year to the stream is estimated to be 3.023 mg/m3 and 4.977 mg/m3, respectively. Uncertainty in the predicted PFBS mass and mass discharge is mainly driven by groundwater flow parameters, especially hydraulic conductivity and recharge. Uncertainties related to initial contaminant conditions and parameters were not systematically assessed and may therefore contribute to the overall uncertainty. Due to the limited number of model realisations, the uncertainty assessment should be regarded as indicative rather than statistically robust. Nevertheless, the results show that PFBS is very mobile may be transported from the source area and may affect downstream drinking water recipients.
Keywords: Groundwater modelling; Groundwater modeling; MODFLOW; MT3DMS; Contaminant transport; Fire extinguishing foam; AFFF; PFAS; PFBS; Uncertainty analysis; Null Space Monte Carlo